ANALISIS PROBLEMATIKA PEMBELAJARAN BAHASA ARAB SISWA MADRASAH IBTIDAIYAH - Parihin Parihin; Nurul Hidayah; Haeruman Rusandi; Hani Nurlaeli (JURNAL MAHASANTRI, 2022)
The purpose of this study was to find out the problems of learning Arabic in Madrasah Ibtidaiyah, the obstacles faced in learning Arabic and how to overcome problems in learning Arabic. This research was conducted in madrasah ibtidaiyah with the data sources were teachers, students and principals. The method used in this research is descriptive qualitative. The problems that exist in learning Arabic do not only lie in the internal factors of students, but also external factors which include the scope of the school and the role of families who pay less attention to their children's education, as well as the influence of the social environment of the community. Therefore, the procedure for collecting data was through observation, interviews, and documentation. After the researchers conducted research and analyzed the data that the authors found in the field, it could be seen that there were several problems in learning Arabic for students, namely students having difficulty reading vocabulary in Arabic, lack of motivation and interest in students' learning of Arabic, allocation of time for learning Arabic. Relatively few Arabic, lack of learning support qualities. Efforts Made to Overcome the Problems of Arabic Learning are memorizing Arabic vocabulary before learning begins, motivating students by doing learning while playing outside the classroom and asking parents for help to guide their children to study at home, procuring the needs of students and teachers towards facilities in stages.